2015
DOI: 10.1128/aem.02734-14
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oxidation Kinetics of Nitrite-Oxidizing Bacteria: Nitrite Availability as a Key Factor in Niche Differentiation

Abstract: Nitrification has an immense impact on nitrogen cycling in natural ecosystems and in wastewater treatment plants. Mathematical models function as tools to capture the complexity of these biological systems, but kinetic parameters especially of nitriteoxidizing bacteria (NOB) are lacking because of a limited number of pure cultures until recently. In this study, we compared the nitrite oxidation kinetics of six pure cultures and one enrichment culture representing three genera of NOB (Nitrobacter, Nitrospira, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
213
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 292 publications
(239 citation statements)
references
References 75 publications
20
213
5
1
Order By: Relevance
“…In particular, the specific rates for AOAs range from 11 to 24 μg N mg − 1 protein h − 1 (Kim et al, 2012), whereas reported rates for Nitrospira spp. range between 16 and 42 μg N mg − 1 protein h − 1 (Nowka et al, 2015). Interesting differences in substrate/product tolerances were observed.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, the specific rates for AOAs range from 11 to 24 μg N mg − 1 protein h − 1 (Kim et al, 2012), whereas reported rates for Nitrospira spp. range between 16 and 42 μg N mg − 1 protein h − 1 (Nowka et al, 2015). Interesting differences in substrate/product tolerances were observed.…”
Section: Discussionmentioning
confidence: 97%
“…So far, investigations on nitrite oxidation kinetics have mainly been based on non-marine pure cultures, enrichment cultures, or natural assembles (Prosser 1989, Both et al 1992, Laanbroek et al 1994, Schramm et al 1999, Blackburne et al 2007, Nowka et al 2015. The aim of this study was to investigate the substrate affinity of marine NOB to link it to environmental conditions and nitrite oxidation kinetics, which thus far has been difficult because nitrite affinity of marine NOB had not yet been investigated in pure cultures.…”
Section: Nitrite Oxidation Kineticsmentioning
confidence: 99%
“…Nitrite oxidation kinetics were calculated based on activity measurements performed after Nowka et al (2015). Nitrospira sp.…”
Section: Activity Measurements and Calculation Of Nitrite Oxidation Kmentioning
confidence: 99%
“…Analyses of Nitrobacter genome sequences provided first insights into the genomic makeup of NOB and revealed a greater metabolic flexibility than anticipated earlier, which included the mixotrophic utilization of various organic substrates (8,9). However, Nitrobacter require high nitrite concentrations (10,11), and molecular surveys indicated that Nitrobacter are not the primary NOB in ecosystems with low ambient nitrite levels such as unfertilized soils (12), freshwater habitats (13), and most WWTPs (14).…”
mentioning
confidence: 99%
“…Nitrospira are well adapted to low nitrite concentrations (10,11) and form at least six phylogenetic lineages (15,16) that are globally distributed in soils (17,18), the oceans (19), freshwater habitats (20), hot springs (16), and many other oxic habitats (15). In addition, Nitrospira members are the key NOB in most WWTPs (14,15).…”
mentioning
confidence: 99%